Density functional theoretical analysis of micro-adsorption of isotopes of hydrogen molecule and atom by uranium. (15th May 2022) - Boda, Anil; Singha Deb, Ashish Kumar; Ali, Sk Musharaf; Shenoy, K.T.
Abstract: Tritium, the heaviest among hydrogen isotopes can be safely stored as metal hydride (tritide). The (depleted) uranium metal is being considered in international thermonuclear experimental reactor (ITER) because of its compatible physicochemical properties. The fundamental understanding of U–H isotopes interaction will help in the efficient storage of H isotopes in depleted uranium metal. Hence, density functional theoretical (DFT) analysis has been performed to investigate the micro-adsorption of hydrogen and its isotopic molecules on uranium atom. The geometrical configurations of UXn, U (X2 )n and UX4 -(X2 )n (X = H, D, T; n = 1–9) cluster were analyzed using different DFT functional (PBE, PBEO, M06 and M06-2X). In the case of U-(H2 )4 and U-(H2 )5, one H2 molecule was seen to be dissociated to give UH2 (H2 )3 and UH2 (H2 )4 cluster as observed earlier in the experiment. The formation of U (X2 )n and UX4 -(X2 )n microclusters was explained by calculating binding enthalpy, natural population analysis and electron density at the bond critical points (BCP). Further, more insights were derived by computing the type of interactions between U and H2 isotopic molecules. The Kubas interaction of a U atom with a H2 molecule was identified by an elongation of the H–H bond without breakage and a reduction in its stretching frequency due to binding. The interaction of U and H2 isotopic molecules was confirmed to be Kubas type of interaction whose strength lies in between the covalent bond of metal hydrides and the van der Waals bond of materials. Further, σ-donation from H2 to d and f orbitals of U atom and π-back-donation from U to the anti-bonding orbital of H2, and atoms-in-molecules analysis indicates that the electron density at the bond critical points of the bound H2 is similar to that of Kubas systems. The Kubas type of interaction suggests that the reversible adsorption of hydrogen molecules might be favored with U metal. From structural and binding enthalpy (BE) analysis, UH4 -(H2 )8 polyhydride was predicted to be the largest super polyhydride and found to be stable by 8.2 kcal/mol over UH4 -(H2 )6 polyhydride and thus confirmed its plausibility. To the best of our knowledge UH4 -(H2 )8 is the largest metal polyhydride ever been reported with twenty hydrogen atoms displaying high gravimetric density of 7.80, 14.47 and 20.21 wt% for H2, D2 and T2 respectively. The present DFT results thus draw further attention for more computational and experimental studies in this important uranium-hydrogen system for efficient reuse of depleted uranium metal as tritium storage material. Graphical abstract: Image 1 Highlights: DFT is used to investigate the micro-adsorption of hydrogen isotopes on uranium. The interaction between U and H2 isotopic molecules is confirmed to be Kubas type. UH4 -(H2 )8 polyhydride is predicted to be the largest super polyhydride. Gravimetric density of 7.80, 14.47 and 20.21 wt% for H2, D2 and T2 is predicted. The reversible adsorption of H2 is favored in U metal due to Kubas type of interaction.